(untitled) (IAHS Medical Journal, 2025)
Background: Psychiatric disorders constitute a higher burden on low and middle-income countries like Bangladesh. Data of psychiatric diseases are poorly recorded and not easily available in countries like Bangladesh. Moreover, different psychiatric diseases are related to various occupations and patients get treatment from service related hospital like Combind Military Hospital (CMH). The objective of the present study is to evaluate the pattern of different psychiatric diseases treated in a tertiary level hospital. Materials and methods: This is a cross sectional type of descriptive study. It was carried out on 379 patients who were treated in Psychiatry Department of CMH, Chattogram. Data of psychiatric patients treated from 1st November 2020 to 31st October 2021 were explored. The diagnoses of different diseases were collected and data were analyzed. Ethical permission was taken prior data collection. Results: Among 379 patients studied, females were 168(44.3%) and males were 211(55.7%), female to male ratio was 0.79:1. Age group distributions showed in both sex psychiatric disorder was highest among 31-40 years age group i.e. 129(34%) , in female maximum patients were 21-30 years age group 66(39.3%) and in male maximum patients were 31-40 years age group 70(33.2%). Monthwise distributions of the patients treated revealed January 6(1.6%), February 6(1.6%), March 3(0.8%), April 33(8.7%), May 34(9.0%), June 72(19%), July 71(18.7%), August 80(21.1%), September 41(10.8%), October 7(1.8%), November 18(4.7.0%) and December 8(2.10%). Most of the patients were treated in June (19%), July (18.7%) & August (21.1%). Common psychiatric findings were Generalized Anxiety Disorder 130(34.30%), Manic Depressive Disorder 59(15.56%), Obsessive Compulsive Disorder 44(12.44%), Bi Mood Disorder 42(11.08%) and Schizophrenia 35 (9.78%), Autism Spectrum Disorder 12(3.58%). GAD 75(44.6%) and OCD 22(13.1%) were commonly observed pattern of psychiatric finding in female. In male common findings were GAD 55(27.5%) and MDD 40(19.8%). Associated findings found in the psychiatric disordered patients were Diabetes Mellitus 75(19.78%), Hypertension 68(17.94%), Headache 65(17.15%), Hypothyroidism 35(9.23%) and Hyperlipidemia 30 (7.91%). Conclusion: There are various types of Psychiatric Disorders treated in psychiatry department in different age group associated with various comorbid diseases needs special care and attention from the physicians for better outcome. IAHS Medical Journal Vol 7(2), December 2024; 100-104